Disappearing Anomaly di Bursa Efek Indonesia - Sukawati, A.A. Rai Niti Darmika; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 32 No 2 (2022)DO - 10.24843/EJA.2022.v32.i02.p08, 2022)
The purpose of this research is to analyze whether there is a disappearing anomaly on the Indonesia Stock Exchange, especially for the Monday effect and January effect. The analysis was carried out by comparing the two anomalies in two periods, namely 2011 to 2015 and 2016 to 2020. The study used a sample of companies that were consistently listed on the Kompas100 Index during the observation period, with a total sample consisting of 42 companies. The analysis technique used is a different test with independent sample t-test. The test results show that the Monday effect in the 2016-2020 period is significantly lower than the Monday effect for the 2011-2015 period, but there is no significant difference in the January effect in the two periods. Keywords: Disappearing Anomaly, January effect, Monday effect .